Assessment Literacy Level of EFL Teachers in Buleleng: A Descriptive Study - Susrini, Putu; Paramartha, Anak Agung Gede Yudha; Wahyuni, Luh Gede Eka (STKIP AGAMA HINDU SINGARAJA, 2022)
This study aimed to investigate the level of assessment literacy possessed by EFL teachers in Buleleng. This study used a descriptive quantitative research approach to answer the research questions. The sample of this study was 40 EFL teachers in Buleleng. The quantitative data were obtained from a set of close-ended questionnaires that contained seven standards of assessment literacy and thirty items of questions. The quantitative data were analyzed using Dixon & Massey (1987) formula, in which the score of EFL teachers was divided into five categories; Very good, Good, Fair, Poor, and Very poor. From this study, it can be obtained that there were 5% of EFL teachers categorized as Very good, 32.5% of EFL teachers categorized as Good, 47.5% of EFL teachers categorized as Fair, 15% of EFL teachers categorized as Poor, and 0% of EFL teachers categorized as Very Poor. The result of this study showed that teacher assessment literacy in Buleleng categorized as “Fair” in general.